Intra-aortic balloon counterpulsation in acute myocardial infarction: old and emerging indications - van Nunen, L. X. (Bohn Stafleu van Loghum, 2013)
BACKGROUND: Recent evidence questions the role of intra-aortic balloon counterpulsation (IABP) in the treatment of acute myocardial infarction (AMI) complicated by cardiogenic shock (CS). An area of increasing interest is the use of IABP for persistent ischaemia (PI). We analysed the use of IABP in patients with AMI complicated by CS or PI. METHODS: From 2008 to 2010, a total of 4076 patients were admitted to our hospital for primary percutaneous coronary intervention (PCI) for AMI. Out of those, 239 patients received an IABP either because of CS or because of PI. Characteristics and outcome of those patients are investigated. RESULTS: The mean age of the study population was 64 ± 11 years; 75 % were male patients. Of the patients, 63 % had CS and 37 % had PI. Patients with CS had a 30-day mortality rate of 36 %; 1-year mortality was 41 %. Patients with PI had a 30-day mortality rate of 7 %; 1-year mortality was 11 %. CONCLUSIONS: Mortality in patients admitted for primary PCI because of AMI complicated by CS is high despite IABP use. Outcome in patients treated with IABP for PI is favourable and mandates further prospective studies.